Oligoclonal bands predict multiple sclerosis in children with optic neuritis - Heußinger, Nicole; Karch, Stephanie (Annals of neurology, 2015)
We retrospectively evaluated predictors of conversion to multiple sclerosis (MS) in 357 children with isolated optic neuritis (ON) as a first demyelinating event who had a median follow-up of 4.0 years. Multiple Cox proportional-hazards regressions revealed abnormal cranial magnet resonance imaging (cMRI; hazard ratio [HR] = 5.94, 95% confidence interval [CI] = 3.39-10.39, p < 0.001), presence of cerebrospinal fluid immunoglobulin G oligoclonal bands (OCB; HR = 3.69, 95% CI = 2.32-5.86, p < 0.001), and age (HR = 1.08 per year of age, 95% CI = 1.02-1.13, p = 0.003) as independent predictors of conversion, whereas sex and laterality (unilateral vs bilateral) had no influence. Combined cMRI and OCB positivity indicated a 26.84-fold higher HR for developing MS compared to double negativity (95% CI = 12.26−58.74, p < 0.001). Accordingly, cerebrospinal fluid analysis may supplement cMRI to determine the risk of MS in children with isolated ON. Ann Neurol 2015;77:1076-1082